2021
DOI: 10.1016/j.jad.2021.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of fear, sadness, and loneliness during the COVID-19 pandemic: Findings from two studies in the UK

Abstract: During the COVID-19 pandemic, exposure to COVID-related stimuli, has been enormous. Exposure to threat-related stimuli, can have a significant impact on people's wellbeing particularly in relation to COVID-related anxiety. The present research comprises two empirical studies. In Study 1, a newly developed Emotional Stroop Task (EST) and an Image Rating Task (IRT) were used to assess, automatic and non-automatic affective responses to COVID-related words and images during the first wave of the pandemic in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“… South Africa Africa Hospital staff N.A. Collectivism Ypsilanti et al, 2021 101 5.5 UK Europe General population 29.10 Individualism Sarıgedik and Bahar Ölmez, 2021 407 13.5 Turkey Europe General population 29.54 Collectivism Guzel et al, 2021 370 12 Turkey Europe Healthcare students N.A. Collectivism Öztekin et al, 2021 479 N.A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… South Africa Africa Hospital staff N.A. Collectivism Ypsilanti et al, 2021 101 5.5 UK Europe General population 29.10 Individualism Sarıgedik and Bahar Ölmez, 2021 407 13.5 Turkey Europe General population 29.54 Collectivism Guzel et al, 2021 370 12 Turkey Europe Healthcare students N.A. Collectivism Öztekin et al, 2021 479 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Also, contrary to what we expected, Middle East samples surprisingly revealed no gender difference in COVID-19 related fear and anxiety. Considering the higher risk perception of females in individualistic societies, their greater awareness of danger, maladaptation in facing threats, and more negative perceptions about the health risks of the pandemics ( Alsharawy et al, 2021 ; Bengston et al, 2005; Magano et al, 2021 ; Morales-Rodríguez, 2021 ; Nino et al, 2021; Orrù et al, 2021 ; Tsipropoulou et al, 2020 ; Ypsilanti et al, 2021 ), and some cultural factors, the highest effect size in favor of females is expected in European samples. In addition, the effect size of gender difference in COVID-19 related fear was higher in individualistic orientation than collectivistic, while in COVID-19 related anxiety was higher in collectivistic orientation than individualistic, but there were no statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SOR model that was proposed by Woodworth and Marquis [ 24 ] defines a stimulus as the external force that influences the psychological state of a person. Ypsilanti, et al [ 25 ] found that affective responses are an effective way to assess the stimulus that is associated with COVID-19, such as feelings of fear, sadness, and loneliness. Evidence of these fears, caused by a perception of threatening stimuli, has already been found in previous pandemic research [ 26 , 27 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%